PHENOLICS IN TWO Alternanthera SPECIES RESIDUES AFFECT THE GERMINATION AND EARLY SEEDLING GROWTH OF RICE (Oryza sativa) - MEHMOOD,A. (2017)
ABSTRACT Alternanthera species are invasive aquatic/semi-aquatic weeds posing a serious threat to agro-biodiversity in several countries in the world. The present study was conducted to assess the phytotoxic effects of Alternanthera philoxeroides and A. sessilis residues on emergence and early seedling growth traits of rice (Oryza sativa). Soil was prepared with 4% (w/w) Alternanthera species residues separately and allowed to decay for 0, 15 and 30 days. Rice emergence was significantly decreased but increase in mean emergence time and time to 50% emergence was observed in soils modified with Alternanthera species residues compared with seed sown in unmodified soils. Rice emergence was reduced to 50-67% and 52-75% by A. sessilis and A. philoxeroides, respectively. A significant reduction in rice root, shoot length, and biomass was also noted with Alternanthera-infested soil. Total phenolics increased with increasing residue decay time in both species thereby showing their direct interaction with emergence and seedling traits of rice. The phenolic compounds identified were namely Quercitin, Chlorogenic acid, P-Coumeric acid, Trans-4-hydroxy3-methoxy, Cinamic acid, Caffeic acid, Syringic acid, Sinapic acid, Vanillic acid, 4-hydroxy-3-methoxy benzoic acid.